PEMETAAN POTENSI PENANGKAPAN IKAN MENGGUNAKAN METODE SINGLE IMAGE (STUDI KASUS: PERAIRAN SELATAN JAWA) - Rahmadani, Nur Aina Rizki; Jaelani , Lalu Muhamad (Geoid, 2020)
Fishing Potential (PPI) is needed to increase fisheries productivity. Traditionally, fishermen use their senses and hereditary habits to determine PPI. Traditionally, fishermen use the five senses and hereditary habits to determine PPI. This method, in addition to being less efficient, can also lead to over-exploitation if fishing is carried out in the same place continuously. The existence of remote sensing technology can be used to determine PPI faster while considering aspects of approval and spatial distribution. One method of determining PPI is based on remote sensing data, mapping the thermal front area first before determining the PPI through manual interpretation based on pixel located between warm and cold water. Manual interpretation has limitations, it depends on humans and takes a long time. To overcome these limitations, in this study, the Single Image Edge Detection (SIED) method developed by Cayulla and Cornillon was applied in the form of a toolbox thus it could be used automatically. Sea Surface Temperature (SPL) data obtained from MODIS Level 2 (6 April 2018) was subsequently processed using this toolbox and successfully developed 22 PPI points in the southern part of Java Island. Meanwhile, PPI detection using the Temperature Gradient Analysis (TGA) method which is done manually produces 28 points. There are 20 locations of the same point using these two methods. Using the SIED method based on the toolbox can improve data, reduce human error with accuracy 64%.